The role of organizational citizenship behavior on employee at government of Aceh - Teuku Aznal; Yusniar Yusniar (Proceedings of AICS - Social Sciences, 2017)
In the effort of improving the human resource (HR) quality through employee commitment, sustainable guidance is required, both the introduction of organizational culture values and also the application of work ethic (especially Islamic work ethics) to the employees involved, including in the development of government of Aceh which becomes  a Measurement  the success of Islamic sharia enforcement in the work environment, where Aceh is the first Areas in Indonesia that uphold the principles of sharia in the community order. The study is focused on measuring Organizational Citizenship Behavior (OCB) by using organizational commitment as mediation factors.  Islamic work ethics variable has the most effect of dominant variable on organizational commitment of employees at government of Aceh and simultaneous verification shows that Islam work ethics and organizational culture simultaneously have positive and significant effects on organizational commitment of employees at government of Aceh.